2021
DOI: 10.1186/s13071-021-04782-7
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of tsetse flies and trypanosome species circulating in the area of Lake Iro in southeastern Chad

Abstract: Background African trypanosomiases are vector-borne diseases that affect humans and livestock in sub-Saharan Africa. Although data have been collected on tsetse fauna as well as trypanosome infections in tsetse flies and mammals in foci of sleeping sickness in Chad, the situation of tsetse fly-transmitted trypanosomes remains unknown in several tsetse-infested areas of Chad. This study was designed to fill this epidemiological knowledge gap by determining the tsetse fauna as well as the trypano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
4
16
1
Order By: Relevance
“…This difference could result from the fact that, female live longer than males [4,32]. Similar ndings have been registered in Chad [30].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This difference could result from the fact that, female live longer than males [4,32]. Similar ndings have been registered in Chad [30].…”
Section: Discussionsupporting
confidence: 77%
“…It is possible that the true infection rate could have been overestimated due to the fact that the whole mosquito was processed by PCR to detect infections. Studies conducted so far indicated different infection rate when screening the midgut, the proboscis, salivary glands or the whole body [23,30]. Moreover because detection of trypanosome DNA was used as a proof of active infection this could also have overestimated the infection rate since dead trypanosomes DNA could have been ampli ed this alongside other factors could have induced overestimation of the infection rate [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflecting this, a large number of studies in different regions have reported the co-circulation of T. brucei , T. congolense and T. vivax , and these have been detected both in surveyed livestock and game animals [ 10 ], as well as in trapped tsetse flies (e.g. [ 11 , 12 ]). The major human infective Plasmodium species, Plasmodium falciparum , in contrast shows strict host specificity although other human infective malaria parasites, such as Plasmodium knowlesi , are more promiscuous and zoonotic.…”
Section: Epidemiology Of Co-infectionmentioning
confidence: 99%
“…The tsetse fly is also a vector of T. vivax , T. simiae , T.b. brucei , and T. congolense , all of which can cause trypanosomiasis in wild and domestic animals (AAT) [ 1 ]. HAT and AAT are severe and sometimes fatal diseases affecting the central nervous system in humans and the nervous system and muscles in animals, respectively.…”
Section: Introductionmentioning
confidence: 99%